Better Understanding the Adoption of the Long-term Athlete Development Model: Case Analyses of Cross-country Ski Coaches - Frankish, Mark T (Université d'Ottawa / University of Ottawa, 2011)
The Long Term Athlete Development (LTAD) model is an innovation created in response to the Canadian Sport Policy (Canadian Heritage, 2007). The LTAD is an “athlete centered, coach driven, and administration, sport science, and sponsor supported” (Canadian Sport Centres, 2006, p. 33) athlete-development model. Since little research has been completed focusing on this model (viz., Black & Holt, 2009) this thesis had the purpose to better understand the adoption of the LTAD by cross-country ski (XCS) coaches. Two articles present a case study of three XCS club’s coaches, and a descriptive qualitative analysis of XCS coaches (N=13). Both analyses used Rogers’ (2003) Diffusion of Innovations theoretical framework to structure the narrative-interview guide, coding structure, and thematic analysis. Two key results of the thesis were an understanding of the link between a club’s characteristics and a coach’s perceived attributes of the LTAD, and secondly a proposed classification system for XCS coaches.
Keywords: Long Term Athlete Development; LTAD; Coaches; Attributes of Adoption; Cross-Country Ski Club